A Matemática escolar nos anos 1920: uma análise de suas disciplinas através das provas dos alunos do Ginásio da Capital do Estado de São Paulo - Santos, Vera Cristina Machado (2003)
This study tries to characterize pedagogical practices in Arithmetic, Algebra, Geometry/Trigonometry in the 1920s, in the oldest official School of the State of São Paulo. These studies analyse questions, which create the Mathematics subject according to the Reformation Francisco Campos . Based upon the field of studies named history of school subjects , the work uses important sources of research from school files, emphasizing students tests and final exams